Conjugated Oligomers and Polymers Sheathed with Designer Side Chains. Issue 9 (14th July 2015) - Pan, Chengjun; Zhao, Chunhui; Takeuchi, Masayuki; Sugiyasu, Kazunori
Abstract Conjugated polymers (CPs) are often referred to as molecular wires because of their quasi one‐dimensional electronic wavefunctions delocalized along the polymer chains. However, in the solid state, CPs tend to self‐assemble through π‐stacking, which greatly attenuates the one‐dimensional nature. By molecular design, CPs can be molecularly insulated just like electric power cords, resulting in so‐called "insulated" molecular wires (IMWs). In this Focus Review, we will discuss their unique photophysical, electronic, and mechanical properties which originate from the absence of π‐stacking.